PENGEMBANGAN E-LKPD INTERAKTIF BERBASIS ETNOMATEMATIKA PADA MATERI BANGUN RUANG TABUNG DENGAN PENGUATAN KARAKTER MANDIRI SISWA KELAS V SDN 3 JATIKALEN - Putri Wardani, Adelia Eko; Ibnu Zaman, Wahid; Afandi, Zainal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The results of observations in class V of SDN 3 Jatikalen show that students face difficulties in understanding the material about building tubes because there is no interactive, innovative and interesting teaching material available for students. This research aims to create an interactive E-LKPD teaching material that integrates cultural elements in mathematics learning in order to optimize students' knowledge of the material. The method used in this research is the R&D method with ADDIE as the model. The data collected includes the validity, practicality and effectiveness of the E-LKPD being developed. The final results of the validation carried out by material experts and media experts obtained an average score of 90.7%, indicating a very valid category. Responses from teachers received an average score of 93.3%. Meanwhile, responses from students in limited trials and extensive trials received an average score of 97% and 97.4%, indicating a very practical category. Effectiveness was measured through a posttest after using the ethnomathematics-based interactive E-LKPD, with an average posttest score of 88.9 and a classical completion rate of 89.5%. Based on the results of the research that has been carried out, a conclusion can be drawn that the development of interactive E-LKPD based on ethnomathematics in learning to build tubes in class V at SDN 3 Jatikalen has proven to be very effective in supporting the teaching and learning process and improving student learning outcomes.